Refunding ETS-proceeds to spur the diffusion of renewable energies: an analysis based on the dynamic oligopolistic electricity market model EMELIE - Thure Traber; Claudia Kemfert (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We use a quantitative electricity market model to analyze the welfare effects of refunding a share of the emission trading proceeds to support renewable energy technologies that are subject to experience effects. We compare effects of supporting renewable energies under both perfect and oligopolistic competition with competitive fringe firms and emission trading regimes that achieve 70 and 80 percent emission reductions by 2050. The results indicate the importance of market power for renewable energy support policy. Under imperfect competition welfare improvements is maximized by refunding ten percent of the emission trading proceeds, while under perfect competition the optimal refunding share is only five percent. However, under both behavioral assumptions we find significant welfare improvements due to experience effects which are induced by the support for renewable energy.
Keywords: 330; Emission trading; renewable energy support; experience effects; imperfect competition; Emissionshandel; Einnahmen; Förderung regenerativer Energien; Regenerative Energie; Innovationsdiffusion; Lernprozess; Elektrizitätswirtschaft; Oligopol; Dynamisches Modell; Wohlfahrtseffekt; Deutschland